Performance in organisational behaviour: strength of work discipline and employee external motivation / Asep Irfan Permana ... [et al.] - -, Asep Irfan Permana; -, Anton Wachidin Widjaja; -, Zahara Tussoleha Rony; -, Irma Setyawati (UiTM Cawangan Johor, 2020)
In principle, operating companies have continued expectations of financial and nonfinancial developments that are supported by human resources performance in organisational behaviour. Analysing phenomenon, this study aims to examine organisational behaviour, namely global leadership, work discipline and external motivation on improving employee performance. Experimental research was carried out through case studies on employees of PT. Ispat Bukit Baja Bekasi. A total of 69 employees were involved in filling through a quantitative questionnaire, by analysing data through Structural Equation Model. The results of the study conveyed that work discipline and external motivation are employee behaviours that are able to improve employee performance, in contrast to global leadership. However, the role of leadership in providing direction and giving examples in behaving act as a key performance indicator of the company. Work discipline and external motivation need to be used by management to strengthen organisational guidelines. In the end, important organisational behaviour is considered by the company, in relation to the performance of the company.